From Motivations to Yield Paths of Tourism Development: The Case of the Algarve - Serra, Jaime (2014)
This paper develops new measurements of tourist yield in the context of the Algarve, which is a sun and sand destination where tourism demand persistently grows, in spite of the signs of destination maturity. This growth contradicts the essence of maturity and drove this research, which attempts to identify the critical preferences which are able to improve destination positioning. According to Pine and Gilmore (1999) in the emerging experience economy, consumers seek unique experiences. This new demand for unique and memorable experiences leads destinations to offer a distinct value-added provision for products and services when they have already achieved a consistent, high level of functional quality. New tourists are more concerned with sophistication, specialization and innovation of tourism products. Thus, because tourism products contain a large number and range of attributes, each tourist experience becomes distinct. Moreover, the overall attractiveness of a destination has long been regarded as a critical criterion in tourism consumer decision making and choice (Crouch, 2011). Hence, the uniqueness of those experiences relies on the declared tourists preferences, which will be treated as motivations in this research (Decrop, 2000; Goodall, 1991; Hsu et al, 2009). However, another stream of research shows that motivations are of paramount importance for the positioning of destinations (Seddighi & Theocharous, 2002), and that these motivations are dynamic (Crompton & McKay, 1997). Motivations and preferences are treated as indistinguishable constructs since we only focus on attributes of the destination and therefore, the tangibility of these motivations may be assumed as preferences. Despite the slight difference outlined by Decrop (2000), it seems widely accepted that motivations may be regarded as comprising two stages, the first one is the driving force that pushes tourists to travel and the other, related with the destination and type of holidays chosen,44 are the so called pull motivations that in essence reflect tourists preferences. Under this theoretical background, pull motivations may be assumed as a proxy for preferences.The contribution of this study lies in the scope of microeconomic theories, namely stated preference theory, which is a descriptive theory in the field of consumer choice as well as in a wide range of other applications within choice-theoretic economics (Hands, 2012). Thus, following this theoretical framework could help the understanding of the role of behavioural variables as proxies of tourist yield when managing and planning tourism destinations for higher competitiveness. On the other hand, this paper also has important managerial implications, in particular in new tourist yield measures for marketing/promotion of the destination.This research starts by exploring the way international tourists value a number of attributes comprised by the Algarve. After identification of the most important attributes, these were evaluated based on the number of overnight stays per tourist and tourist daily spending. This research is supported by secondary data, provided by a self-administrated questionnaire survey applied to international tourists during their departure from Faro international airport. The methodology included a first selection of the motivations that present higher heterogeneity acrossyears. The sample consists of 15542 observations collected from 2007 to 2010 (Correia & Pimpão, 2012). Therefore, this paper identifies the high-yield visitors by country based on tourist preferences. Previous results reveal that preferences with higher yield expenditure markets are: sightseeing and excursions; information available; price; accommodation; and gastronomy. In this light, the aims of this study are: - to identify patterns of value-added given by international tourists for each motivation; - to analyse the high-yield visitors by motivations across nationalities; - to contribute to the understanding of how the yield potential of different source markets and segments can underpin destination marketing by destination sector organisations.